Kansas Land Prices and Cash Rental Rates - Dhuyvetter, Kevin C.; Kastens, Terry L. (My University, 2000)
This farm management guide reports Kansas land prices from 1981-2000 and cash rental rates for 1981-1999. The data is meant to be useful to farm managers.
MF1100_2000_10
Keywords: MF1100; Economics; MF